Studi Kelayakan Struktur Dermaga Meulaboh Aceh Terhadap Beban Layan - Pasaribu, Humisar; Bartolomeus, Bartolomeus; Purba, Luki Hariando (Jurnal Ilmiah Rekayasa Sipil, 2024)
This research aims to conduct a feasibility study on the Meulaboh port dock in Aceh. The port dock is a key infrastructure in supporting shipping and trade activities in the region. With continued economic growth and changing trade patterns, it is important to evaluate the feasibility and need to upgrade the Meulaboh port dock. The port dock feasibility study involves reviewing several analytical aspects, including technical, economic, environmental, and social aspects. However, in this research, the researcher only reviewed the technical aspects. Researchers will evaluate the physical condition and capacity of the pier so that barges can dock safely. The research methodology involved field surveys, secondary data analysis, and interviews with relevant stakeholders. It is hoped that the results of this research can provide clear guidance for decision-making regarding investment and development of the Meulaboh port pier.The research entitled Feasibility Study of the Meulaboh-Aceh Port Pier resulted in the conclusion that the pier can be berthed by barges measuring 270 feet. It is hoped that the results of this research can also be a basis for intelligent decision-making in efforts to improve and develop this important port infrastructure. The results of this research indicate that there has been damage to the jetty pier structure and significant corrosion to the breasting dolphin structure. The deformation due to service loads is very large in the damaged area of the pier jetty structure so it will definitely endanger users. Recommendations for this pier to continue functioning as public infrastructure require repairs.